PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN MEMBELI KOSMETIK BB CREAM WARDAH DI KOTA PALU - lestari, Suci fidiah (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
Suci Fidiah Lestari. "The Effect of Product Quality on Consumer Satisfaction on Buying BB Cream Wardah Cosmetics in Palu City."Supervised by Maskuri Sutomo and Farid.This study aims to determine the effect of product quality which consists of performance, features, reliability, suitability, serviceability, durability, aesthetics, perception of quality on customer satisfaction buying BB Cream Wardah cosmetics in Palu City. The type of research used is quantitative (shows the relationship between variables). The population in this study were all users and buyers of BB Cream Wardah in Palu City. The sampling technique in this study uses purposive sampling, with a total sample of 90 respondents. Retrieval of data using a questionnaire. The analytical method used is multiple linear regression analysis, F test, and t test. The results showed that performance, features, reliability, suitability, serviceability, durability, aesthetics, perceived quality had a significant effect on consumers' satisfaction of buying BB Cream Wardah cosmetics in Palu City simultaneously or partially.